2022
DOI: 10.1021/acs.chemrestox.1c00309
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Redox-Active Duroquinone from Vaping of Vitamin E Acetate Contributes to Oxidative Lung Injury

Abstract: In late 2019, the outbreak of e-cigarette or vaping-associated lung injuries (EVALIs) in the United States demonstrated to the public the potential health risks of vaping. While studies since the outbreak have identified vitamin E acetate (VEA), a diluent of tetrahydrocannabinol (THC) in vape cartridges, as a potential contributor to lung injuries, the molecular mechanisms through which VEA may cause damage are still unclear. Recent studies have found that the thermal degradation of e-liquids during vaping can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 63 publications
0
20
1
Order By: Relevance
“…THC has a stronger tendency to degrade compared to VEA. Regarding ketene that has been suggested to be formed by vaping or pyrolytic heating of VEA, it is not clear whether it is identifiable with our methods or is not formed at the temperatures tested here. Products like duroquinone and durohydroquinone , are reported to be formed below a vaping coil temperature of 300 °C; however, we do not observe them with the preparation or detection methods used in this work. The selectivity and solubility of GC-MS extraction solvent could be a reason why products like quinones were not observed in the current study.…”
Section: Discussioncontrasting
confidence: 65%
“…THC has a stronger tendency to degrade compared to VEA. Regarding ketene that has been suggested to be formed by vaping or pyrolytic heating of VEA, it is not clear whether it is identifiable with our methods or is not formed at the temperatures tested here. Products like duroquinone and durohydroquinone , are reported to be formed below a vaping coil temperature of 300 °C; however, we do not observe them with the preparation or detection methods used in this work. The selectivity and solubility of GC-MS extraction solvent could be a reason why products like quinones were not observed in the current study.…”
Section: Discussioncontrasting
confidence: 65%
“…However, our results clearly demonstrate degradation of VEA and formation of products such as DQ at 176˚C, indicating that the device itself may play a larger role in the decomposition of VEA than initially anticipated. Previous study in our lab has also found substantial formation of DQ at 218˚C-several hundred degrees lower than what has been predicted [24]. To further understand if the device itself may impact the thermal degradation of VEA, pure pyrolysis of VEA oil was carried out using a tube furnace reactor.…”
Section: Potential Catalysis Of Vea Vaping Pyrolysismentioning
confidence: 92%
“…The vaping emissions were collected using a cold trap apparatus maintained at -40˚C (Across International LLC). The particle collection efficiency of the cold trap system at the flow rate used in this study has been reported previously (� 99% by volume) [24]. To collect aerosol emissions, one 4 s puff was taken at intervals of 1 min to maintain consistency with the temperature measurement procedure.…”
Section: E-cigarette Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ketene does not survive long enough to be detected intact in vivo . Chemical and physical studies such as reported herein and by others , are thus needed to elucidate sources of exposure.…”
mentioning
confidence: 99%